Increasing Competency Of SD Teachers In Thematic Learning Planning Through Group Supervision Using Collaborative Approaches In SDN Tlambah 2 Karangpenang Sampang - Namin Namin (KABILAH : Journal of Social Community, 2019)
Abstrak: Penelitian ini dilakukan dengan tujuan meningkatkan kompetensi guru di SDN Tlambah 2, Kabupaten Karangpenang Sampang. Perencanaan pembelajaran tematik dalam meningkatkan kualitas pembelajaran tematik. Subjek penelitian dalam penelitian tindakan kelas ini adalah guru kelas di Sekolah Dasar Negeri Tlambah 2, Kabupaten Karangpenang Sampang. Penelitian tindakan kelas ini dilaksanakan dalam dua siklus, menggunakan tahapan perencanaan, tindakan, observasi dan refleksi dalam setiap siklus. Data yang terkumpul dianalisis secara kuantitatif dan kualitatif. Dari penelitian tindakan kelas ini disimpulkan bahwa supervisi kelompok dengan pendekatan kolaboratif dapat meningkatkan kompetensi guru kelas di SDN Tlambah 2 Kabupaten Karangpenang Sampang. Kata kunci: kolaboratif, kompetensi, tematik Abstract: This research was conducted with the aim of increasing the competency of teachers in SDN Tlambah 2, Karangpenang Sampang District, Spreading thematic learning planning in improving the quality of thematic learning. Research subjects in this action research are low grade teachers in Tlambah 2 Public Elementary School, Karangpenang Sampang District. School action research means it is carried out in two cycles, using the stages of planning, action, observation and reflection in each cycle. The collected data is analyzed quantitatively and qualitatively. From this school action research concludes that group supervision with a collaborative approach can improve the competence of classroom teachers in SDN Tlambah 2, Karangpenang Sampang District. Keywords: collaborative, competence, thematic